DIDACTIC CONDITIONS OF IMPLEMENTATION COMPUTER TECHNOLOGIES IN PROFESSIONAL TRAINING FUTURE MUSIC TEACHER - L.I. Varnavska (Academy of Cognitive and Natural Sciences, 2022)
This article is examining didactic resources of synthesizer as a tool of formation of harmonic and timbre dynamic hearing of prospective teacher of music; the essence of assembling method as the mean of creative activity in conditions of latest technologies implementation is also revealed.